Development of an Emergency Medicine Simulation Fellowship Consensus Curriculum: Initiative of the Society for Academic Emergency Medicine Simulation Academy. (6th September 2016) - Frallicciardi, Alise; Vora, Samreen; Bentley, Suzanne; Nadir, Nur‐Ain; Cassara, Michael; Hart, Danielle; Park, Chan; Cheng, Adam; Aghera, Amish; Moadel, Tiffany; Dobiesz, Valerie
Abstract: Objectives: There is currently no consolidated list of existing simulation fellowship programs in emergency medicine (EM). In addition, there are no universally accepted or expected standards for core curricular content. The objective of this project is to develop consensus‐based core content for EM simulation fellowships to help frame the critical components of such training programs. Methods: This paper delineates the process used to develop consensus curriculum content for EM simulation fellowships. EM simulation fellowship curricula were collected. Curricular content was reviewed and compiled by simulation experts and validated utilizing survey methodology, and consensus was obtained using a modified Delphi methodology. Results: Fifteen EM simulation fellowship curricula were obtained and analyzed. Two rounds of a modified Delphi survey were conducted. The final proposed core curriculum content contains 47 elements in nine domains with 14 optional elements. Conclusion: The proposed consensus content will provide current and future fellowships a foundation on which to build their own specific and detailed fellowship curricula. Such standardization will ultimately increase the transparency of training programs for future trainees and potential employers.